DNAJB1–PRKACA fusion kinase interacts with β-catenin and the liver regenerative response to drive fibrolamellar hepatocellular carcinoma - Edward R. Kastenhuber; Gadi Lalazar; Shauna L Houlihan; Darjus F. Tschaharganeh; Timour Baslan; Chi-Chao Chen; David Requena; Sha Tian; Benedikt Bosbach; John E. Wilkinson; Sanford M. Simon; Scott W. Lowe (2017)
Significance Efforts to understand and treat fibrolamellar hepatocellular carcinoma (FL-HCC) have been confounded by a lack of models that accurately reflect the genetics and biology of the disease. Here we demonstrate that the Dnajb1–Prkaca gene fusion drives tumorigenesis in mice, and that fusion to DNAJB1 drives FL-HCC initiation more effectively than wild-type PRKACA overexpression. The requirement of the PRKACA kinase domain in tumor initiation establishes the potential utility of kinase inhibitors targeting the fusion. By identifying genetic and environmental factors that can enhance the consistency and aggressiveness of disease progression, we reveal biological characteristics of the disease and advance a robust platform for future preclinical studies.